Protecting procedural care—cybersecurity considerations for robotic surgery - Gordon, William J.; Ikoma, Naruhiko; Lyu, Heather; Jackson, Gretchen Purcell; Landman, Adam (NPJ digital medicine, 2022)
Cybersecurity is an increasingly important concern for reliable healthcare delivery and is particularly salient for robotic surgery. Surgical robots are complex systems with numerous points of vulnerability, and there have been real-world demonstrations of successful cyberattacks on surgical robots. There are several ways to improve the risk profile of robotic surgery, including recognizing system complexity, investing in regular software updates, following cybersecurity best-practices, and increasing transparency for all stakeholders. As robotic surgery continues to technologically advance, ensuring overall system safety from a cybersecurity perspective is paramount.